Engineered Extracellular Matrices as Biomaterials of Tunable Composition and Function. (11th January 2017) - Bourgine, Paul Emile; Gaudiello, Emanuele; Pippenger, Benjamin; Jaquiery, Claude; Klein, Thibaut; Pigeot, Sebastien; Todorov, Atanas; Feliciano, Sandra; Banfi, Andrea; Martin, Ivan
Abstract : Engineered and decellularized extracellular matrices (ECM) are receiving increasing interest in regenerative medicine as materials capable to induce cell growth/differentiation and tissue repair by physiological presentation of embedded cues. However, ECM production/decellularization processes and control over their composition remain primary challenges. This study reports engineering of ECM materials with customized properties, based on genetic manipulation of immortalized and death‐inducible human mesenchymal stromal cells (hMSC), cultured within 3D porous scaffolds under perfusion flow. The strategy allows for robust ECM deposition and subsequent decellularization by deliberate cell‐apoptosis induction. As compared to standard production and freeze/thaw treatment, this grants superior preservation of ECM, leading to enhanced bone formation upon implantation in calvarial defects. Tunability of ECM composition and function is exemplified by modification of the cell line to overexpress vascular endothelial growth factor alpha (VEGF), which results in selective ECM enrichment and superior vasculature recruitment in an ectopic implantation model. hMSC lines culture under perfusion‐flow is pivotal to achieve uniform scaffold decoration with ECM and to streamline the different engineering/decellularization phases in a single environmental chamber. The findings outline the paradigm of combining suitable cell lines and bioreactor systems for generating ECM‐based off‐the‐shelf materials, with custom set of signals designed to activate endogenous regenerative processes. Abstract : The biological functionality of scaffold materials can be enhanced and customized by decoration with cell‐laid extracellular matrix (ECM) . As proof‐of‐principle of the concept, a death‐inducible mesenchymal stromal cell line (MSOD), or its counterpart overexpressing VEGF, are cultured under perfusion flow and induced to apoptosis. The resulting decellularized, customized ECM grafts are used to regenerate bone tissue or to enhance vascularization.